Hadith #2176 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ﷺ) said, “The honest treasurer who gives willingly what he is ordered to give, is one of the two charitable persons, (the second being the owner).
Grade: Sahih

Hadith #2177 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
I went to the Prophet (ﷺ) with two men from Ash`ari tribe. I said (to the Prophet), “I do not know that they want employment.” The Prophet (ﷺ) said, “No, we do not appoint for our jobs anybody who demands it earnestly.”
Grade: Sahih

Hadith #2178 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Allah did not send any prophet but shepherded sheep.” His companions asked him, “Did you do the same?” The Prophet (ﷺ) replied, “Yes, I used to shepherd the sheep of the people of Mecca for some Qirats.”
Grade: Sahih

Hadith #2179 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) and Abu Bakr employed a (pagan) man from the tribe of Bani Ad-Dail and the tribe of Bani ‘Abu bin `Adi as a guide. He was an expert guide and he broke the oath contract which he had to abide by with the tribe of Al-`Asi bin Wail and he was on the religion of Quraish pagans. The Prophet (ﷺ) and Abu Bakr had confidence in him and gave him their riding camels and told him to bring them to the Cave of Thaur after three days. So, he brought them their two riding camels after thr
Grade: Sahih

Hadith #2180 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
(the wife of the Prophet) Allah’s Messenger (ﷺ) and Abu Bakr hired a man from the tribe of Bani-Ad-Dil as an expert guide who was a pagan (follower of the religion of the pagans of Quraish). The Prophet (ﷺ) and Abu Bakr gave him their two riding camels and took a promise from him to bring their riding camels in the morning of the third day to the Cave of Thaur.
Grade: Sahih

Hadith #2181 - Sahih al-Bukhari - Ya'la bin 'Ata' يعلى بن عطاء العامري (Sahih al-Bukhari)
I fought in Jaish-al-Usra (Ghazwa of Tabuk) along with the Prophet (ﷺ) and in my opinion that was the best of my deeds. Then I had an employee, who quarrel led with someone and one of the them bit and cut the other’s finger and caused his own tooth to fall out. He then went to the Prophet (with a complaint) but the Prophet (ﷺ) canceled the suit and said to the complainant, “Did you expect him to let his finger in your mouth so that you might snap and cut it (as does a stallion camel)?”
Grade: Sahih

Hadith #2182 - Sahih al-Bukhari - Ubayy ibn Ka'b (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Both of them (Moses and Al-Khadir) proceeded on till they reached a wall which was about to fall.” Sa`d said , “(Al-Khadir pointed) with his hands (towards the wall) and then raised his hands and the wall became straightened up.” Ya`la said, “I think Sa`id [?? or Sa`d] said, ‘He (Khadir) passed his hand over it and it was straightened up.” (Moses said to him), “if you had wanted, you could have taken wages for it.” Sa`id said, “Wages with whic
Grade: Sahih

Hadith #2183 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Your example and the example of the people of the two Scriptures (i.e. Jews and Christians) is like the example of a man who employed some laborers and asked them, ‘Who will work for me from morning till midday for one Qirat?’ The Jews accepted and carried out the work. He then asked, Who will work for me from midday up to the `Asr prayer for one Qirat?’ The Christians accepted and fulfilled the work. He then said, ‘Who will work for me from the `Asr till sunse
Grade: Sahih

Hadith #2184 - Sahih al-Bukhari - Abdullah ibn Umar ibn al-Khattab (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Your example and the example of Jews and Christians is like the example of a man who employed some laborers to whom he said, ‘Who will work for me up to midday for one Qirat each?’ The Jews carried out the work for one Qirat each; and then the Christians carried out the work up to the `Asr prayer for one Qirat each; and now you Muslims are working from the `Asr prayer up to sunset for two Qirats each. The Jews and Christians got angry and said, ‘We work m
Grade: Sahih

Hadith #2185 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Allah said, ‘I will be an opponent to three types of people on the Day of Resurrection: -1. One who makes a covenant in My Name, but proves treacherous; -2. One who sells a free person and eats his price; and -3. One who employs a laborer and takes full work from him but does not pay him for his lab our.’ “
Grade: Sahih

Hadith #2186 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ﷺ) said, “The example of Muslims, Jews and Christians is like the example of a man who employed laborers to work for him from morning till night for specific wages. They worked till midday and then said, ‘We do not need your money which you have fixed for us and let whatever we have done be annulled.’ The man said to them, ‘Don’t quit the work, but complete the rest of it and take your full wages.’ But they refused and went away. The man employed another batch after th
Grade: Sahih

Hadith #2187 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “Three men from among those who were before you, set out together till they reached a cave at night and entered it. A big rock rolled down the mountain and closed the mouth of the cave. They said (to each other), Nothing could save you from this rock but to invoke Allah by giving reference to the righteous deed which you have done (for Allah’s sake only).’ So, one of them said, ‘O Allah! I had old parents and I never provided my family (wife, chi
Grade: Sahih

Hadith #2188 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Whenever Allah’s Messenger (ﷺ) ordered us to give in charity we would go to the market and work as porters to earn a Mudd (two handfuls) (of foodstuff) but now some of us have one-hundred thousand Dirhams or Diners. (The sub-narrator) Shaqiq said, “I think Abu Mas`ud meant himself by saying (some of us) .
Grade: Sahih

Hadith #2189 - Sahih al-Bukhari - Tawus bin Kaysan طاوس (Sahih al-Bukhari)
Ibn `Abbas said, “The Prophet (ﷺ) forbade the meeting of caravans (on the way) and ordained that no townsman is permitted to sell things on behalf of a bedouin.” I asked Ibn `Abbas, “What is the meaning of his saying, ‘No townsman is permitted to sell things on behalf of a bedouin.’ ” He replied, “He should not work as a broker for him.”
Grade: Sahih

Hadith #2190 - Sahih al-Bukhari - Khabbab ibn al-Aratt (Sahih al-Bukhari)
I was a blacksmith and did some work for Al-`As bin Wail. When he owed me some money for my work, I went to him to ask for that amount. He said, “I will not pay you unless you disbelieve in Muhammad.” I said, “By Allah! I will never do that till you die and be resurrected.” He said, “Will I be dead and then resurrected after my death?” I said, “Yes.” He said, “There I will have property and offspring and then I will pay you your due.” Then Allah revealed. ‘Have you seen him
Grade: Sahih

Hadith #2191 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
Some of the companions of the Prophet (ﷺ) went on a journey till they reached some of the ‘Arab tribes (at night). They asked the latter to treat them as their guests but they refused. The chief of that tribe was then bitten by a snake (or stung by a scorpion) and they tried their best to cure him but in vain. Some of them said (to the others), “Nothing has benefited him, will you go to the people who resided here at night, it may be that some of them might possess something (as treatment)
Grade: Sahih

Hadith #2192 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
When Abu Taiba cupped the Prophet (ﷺ) and the Prophet (ﷺ) ordered that he be paid one or two Sas of foodstuff and he interceded with his masters to reduce his taxes.
Grade: Sahih

Hadith #2193 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
When the Prophet (ﷺ) was cupped, he paid the man who cupped him his wages.
Grade: Sahih

Hadith #2194 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
When the Prophet (ﷺ) was cupped, he paid the man who cupped him his wages. If it had been undesirable he would not have paid him.
Grade: Sahih

Hadith #2195 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ﷺ) used to get cupped and would never withhold the wages of any person .
Grade: Sahih

Hadith #2196 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ﷺ) sent for a slave who had the profession of cupping, and he cupped him. The Prophet (ﷺ) ordered that he be paid one or two Sas, or one or two Mudds of foodstuff, and appealed to his masters to reduce his taxes:
Grade: Sahih

Hadith #2197 - Sahih al-Bukhari - Abu Mas'ud al-Ansari (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) regarded illegal the price of a dog, the earnings of a prostitute, and the charges taken by a soothsayer.
Grade: Sahih

Hadith #2198 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) prohibited the earnings of slave girls (through prostitution).
Grade: Sahih

Hadith #2199 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
The Prophet (ﷺ) forbade taking a price for animal copulation.
Grade: Sahih

Hadith #2200 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
“Allah’s Messenger (ﷺ) gave the land of Khaibar to the Jews to work on and cultivate and take half of its yield. Ibn `Umar added, “The land used to be rented for a certain portion (of its yield).” Nafi` mentioned the amount of the portion but I forgot it. Rafi` bin Khadij said, “The Prophet (ﷺ) forbade renting farms.” Narrated ‘Ubaidullah Nafi` said: Ibn `Umar said: (The contract of Khaibar continued) till `Umar evacuated the Jews (from Khaibar).
Grade: Sahih